Analisis Modal Kerja Pada UMKM Cookies & Dessert By Me Dalam Meningkatkan Laba Usaha - Chofifah, Astin Dewi; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Economic growth is a measuring tool in measuring a country's development. A business has a major role in development. To achieve the desired goals, the company's capabilities must be able to maximize and utilize properly by management, one of which is related to managing working capital. that the profit level of MSMEs is significantly influenced by their working capital management, when the capital used for the production process continues to increase, the production output will continue to increase, and allow increased profits. Determining the importance of MSMEs in processing and allocating working capital to increase business income is the main objective of this study. the method used is quantitative descriptive by describing a variable without the need to test certain hypotheses. So from the results and discussions that have been carried out, the level of working capital at Dessert & Cookies by Me has fluctuated during the January-April 2024 period which is not significant. The use of working capital is used for the purchase of raw materials, equipment maintenance and employee salary costs. Net profit at UMKM Dessert & Cookies by Me for the period January-April 2024 continues to increase in line with its business operating costs.